1988
DOI: 10.1002/art.1780310908
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of the effects of a supervised cardiovascular fitness training program on the manifestations of primary fibromyalgia

Abstract: Forty-two patients with primary fibromyalgia were randomized into a 20-week program consisting of either cardiovascular fitness (CVR) training or simple flexibility exercises (FLEX) that did not lead to enhanced cardiovascular fitness. Patients were supervised by the same medical fitness instructors. Patients in neither group had contact with members of the other group, and were blinded as to the exercise taught to the alternative group. Groups met for 60 minutes 3 times each week. The compliance rate was 90%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
169
2
32

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(209 citation statements)
references
References 15 publications
5
169
2
32
Order By: Relevance
“…Preliminary studies of children (24) and adults (25) with fibromyalgia have suggested that cognitive-behavioral treatments should be effective. Based on research with adult patients (26), interventions should also target cardiovascular conditioning and flexibility. In contrast with what Gedalia et a1 (27) have suggested, the efficacy of psychologically based treatments neither confirms, nor denies, an underlying psychological basis for a disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies of children (24) and adults (25) with fibromyalgia have suggested that cognitive-behavioral treatments should be effective. Based on research with adult patients (26), interventions should also target cardiovascular conditioning and flexibility. In contrast with what Gedalia et a1 (27) have suggested, the efficacy of psychologically based treatments neither confirms, nor denies, an underlying psychological basis for a disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise is another clinical strategy that has been shown to have a number of positive effects on health and well-being across many health conditions, and efforts to bolster physical activation and functioning are common in multifaceted programmes for chronic symptoms and disability (McCain et al 1988;Fulcher & White 1997;Frost et al 1998;Wearden et al 1998). Evidence favours supervised, graduated and early return to work for improving role functioning among patients with chronic symptoms and disability.…”
Section: (D) Intensive Rehabilitative Carementioning
confidence: 99%
“…Este estudo demonstrou que a privação do sono diminuia o limiar de dor em sedentá-rios, mas o mesmo não acontecia em indivíduos treinados. Apenas uma década mais tarde, ensaios clínicos foram publicados demonstrando que exercícios aeróbios diminuem a dor na FM (6) . A Tabela 1 sintetiza os resultados, desenhos, instrumentos e desfechos dos principais estudos sobre exercício na FM, desde 1988FM, desde até 2005 Nos últimos 20 anos, foram publicados 28 ensaios clínicos sobre exercício no tratamento da FM, incluindo aproximadamente 1500 pacientes.…”
Section: Introductionunclassified
“…A Tabela 1 sintetiza os resultados, desenhos, instrumentos e desfechos dos principais estudos sobre exercício na FM, desde 1988FM, desde até 2005 Nos últimos 20 anos, foram publicados 28 ensaios clínicos sobre exercício no tratamento da FM, incluindo aproximadamente 1500 pacientes. Desses, 12 avaliaram o condicionamento aeróbio (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) …”
unclassified